Pengaruh Modal Kerja, Tenaga Kerja, dan Luas Lahan Terhadap Produktivitas Petani Garam Tradisional di Desa Purwakerti - Ni Ketut Puspita Rini; M. Rudi Irwansyah (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of working capital, labor, and land area on the productivity of traditional salt farmers in Purwakerti Village, both partially and simultaneously. This study uses a quantitative approach with a type of causal research. The population in this study is all salt farmers in Purwakerti Village, with a sample of 31 respondents. The sampling technique used is the saturated sampling method, where the entire population is sampled. The type of data used is quantitative data, with data sources derived from primary and secondary data. Data collection is carried out through the dissemination of questionnaires, documentation, and observation. The analysis technique used is multiple linear regression with partial (t-test) and simultaneous (F-test) hypothesis testing. The results of the study show that: (1) Working capital has a positive and significant effect on the productivity of salt farmers, (2) Labor has a negative and significant effect on the productivity of salt farmers, (3) Land area has a positive and significant effect on the productivity of salt farmers, and (4) Working capital, labor, and land area simultaneously have a significant effect on the productivity of salt farmers in Purwakerti Village.